Small scale farming in Kédougou, South-East Senegal - Lisa Guardone; Elisa Gasparoni; Antonio Barsanti; Jean-Pierre Boubane; Ousseynou Ba; Ismael Tiaw; Cristiano Rossignoli; Francesco Di Iacovo (Journal of Agriculture and Environment for International Development)
Livestock is essential to global small scale farmers’ livelihoods. In Senegal, despite an increasing urbanisation, half of the population lives in rural areas relying on agricultural activities. The present work, which was carried out in the framework of a development project in the Kédougou region (South-East Senegal), analyses activities supporting small scale poultry farming performed in 30 groups of 10 households within the project and evaluates the effects of such interventions, in order to identify the most relevant factors contributing to increase Food and Nutrition Security. Despite difficulties, mainly related to climatic and social-economic conditions, a modest level of success was obtained, as over one third of the groups were able to produce chickens for self-consumption or for sale for minimum 6 continuous months. A positive effect was observed for social relations, improved in most of the 30 groups. Shortcomings and lessons learned are also presented.